PENYELENGGARAAN PENGELOLAAN KEUANGAN DAERAH PADA PEMERINTAH DAERAH PROVINSI RIAU - Maulidiah, Sri (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2017)
In mengimplemantasikan of related/relevant governmental policy with management of area finance, hence Local Government of Provinsi Riau take policy in the form of Regulation of Governor of Riau of Number 54 Year 2007 about System and Procedure of Monetary Management [of] Area, in order to management of finance of area own system, procedure, and the clear arrangement. According to trust Section 4 sentence ( 1) Permendagri of Number 13 Year 2006 about Guidance of Monetary Management [of] Area, sounding; finance of Area managed orderlyly, meekly the legislation, effective, efficient, economic, transparent, and bertanggungjawab paid attention toly [is] justice ground, making proper, and the benefit to socialize. management of governmental Policy about Guidance of Monetary Management [of] Area, owning dimenssi: Budget Planning, Budget Execution, Penatausahaan Budget, Reporting And Pertanggung of answer of Budget and also Observation and Budget Construction. Pursuant to analysis of management of management of finance [of] [at] Local Government of Riau still uncommitt maximally, from five dimension that is Planning, Execution, Penatausahaan, Reporting And Responsibility and Observation and Budget Construction, only Penatausahaan of Budget fulfilling standard of regulation rule. As for resistance in management of management of finance of area [of] [at] local government of Provinsi Riau, among other things: Lack of socialization, lack of book of Juklak and Juknis of area of management of area finance, lack of understanding [of] about execution of activity base on performance, delay in pemberitahua compile Cash Budget Device ( RACK).